Effects of mixed cultivation mode and nutrient condition optimization on biomass accumulation and lipid content of Tetradesmus obliquus - Shuyuan LI; Dan ZHAO; Canmei WANG; Ting YUAN; Xiangmeng MA; Qun WEI (能源环境保护)
Microalgae are considered to be the most promising feedstock for biodiesel production due to their advantages in high photosynthetic efficiency, growth rate, and lipid accumulation rate, which can alleviate the environmental pollution caused by fossil fuels. To increase the biomass, lipid content, and high-value product yield of microalgae, it is necessary to optimize their cultivation modes and nutritional conditions. This study investigated the optimal cultivation mode for the growth of Tetradesmus obliquus under three conditions: autotrophic, mixotrophic, and heterotrophic. Additionally, response surface methodology was employed to optimize the nutrient conditions for cultivation, with the goal of improving the biomass and lipid content of microalgae. The results showed that mixotrophic cultivation was the most suitable mode for the growth and development of Tetradesmus obliquus. Under mixotrophic cultivation conditions for 24 hours, the biomass and lipid content of microalgae were 3.82 times and 2.49 times higher, respectively, compared to autotrophic cultivation conditions. Moreover, the highest protein production during the logarithmic growth phase was the highest in the 8-hour mixotrophic and 16-hour autotrophic combination, reaching 554.87 mg·L−1. By optimizing the nutritional substances using response surface methodology, the optimal parameters under mixotrophic conditions were as follows: Carbon-to-nitrogen ratio of 10, trace element addition of 0.1 mL, and vitamin addition of 1.0 mL. The measured biomass and predicted values were 2.45 g·L−1 and 2.43 g·L−1, respectively. The optimization of mixotrophic cultivation mode and nutritional conditions could enhance microalgae biomass and utilization efficiency.